Efficient and regioselective one-step synthesis of 7-aryl-5-methyl- and 5-aryl-7-methyl-2-amino-[1, 2, 4]triazolo[1, 5-a]pyrimidine derivatives. Issue 37 (13th September 2017) - Massari, Serena; Desantis, Jenny; Nannetti, Giulio; Sabatini, Stefano; Tortorella, Sara; Goracci, Laura; Cecchetti, Violetta; Loregian, Arianna; Tabarrini, Oriana
Abstract : Two facile and efficient one-step procedures for the regioselective synthesis of 7-aryl-5-methyl- and 5-aryl-7-methyl-2-amino-[1, 2, 4]triazolo[1, 5- a ]pyrimidines. Abstract : Two facile and efficient one-step procedures for the regioselective synthesis of 7-aryl-5-methyl- and 5-aryl-7-methyl-2-amino-[1, 2, 4]triazolo[1, 5- a ]pyrimidines have been developed, via reactions of 3, 5-diamino-1, 2, 4-triazole with variously substituted 1-aryl-1, 3-butanediones and 1-aryl-2-buten-1-ones, respectively. The excellent yield and/or regioselectivity shown by the reactions decreased when ethyl 5-amino-1, 2, 4-triazole-3-carboxylate was used. [1, 2, 4]Triazolo[1, 5- a ]pyrimidine being a privileged scaffold, the procedures herein reported may be useful for the preparation of biologically active compounds. In this study, the preparation of a set of compounds based on the [1, 2, 4]triazolo[1, 5- a ]pyrimidine scaffold led to the identification of compound20 endowed with a very promising ability to inhibit influenza virus RNA polymerase PA–PB1 subunit heterodimerization.